IMPACT OF ENVIRONMENTAL REGULATION ON ECONOMIC GROWTH IN THE YANGTZE RIVER DELTA - ’An, Xi (International Journal of Allied Research in Economics (IJARE), 2023)
China's economic landscape faces significant challenges due to its detachment from the United States, resulting in a prolonged period of economic downturn. Responding to this situation, the Political Bureau of the CPC Central Committee has introduced the concept of "internal circulation," aimed at bolstering domestic demand and generating fresh impetus for economic growth. This research delves into the connection between environmental regulations and high-quality economic development. It conducts a thorough analysis of panel data spanning 18 years across 33 cities in the Yangtze River Delta region. The study employs the entropy method to construct comprehensive indices for measuring both high-quality economic growth and environmental regulation. Additionally, the research employs the variance inflation factor test to identify and address multicollinearity. The findings of this study hold substantial significance for policymakers striving to achieve economic development that is both high-quality and environmentally sustainable. The results underscore that environmental regulation can serve as a novel catalyst for high-quality economic growth, emphasizing the continued importance of reinforcing such regulations. As a recommendation, policymakers are urged to prioritize environmental protection in their decision-making processes, aiming for a harmonious balance between economic growth and environmental sustainability.